Coordination of oxysterol binding protein 1 and VAP-A/B modulates the generation of cholesterol and viral inclusion bodies to promote grass carp reovirus replication - Li, Jia Qi; Zhang, Jie; Chen, Yang; Le, Tao; Chang, Ming Xian (Frontiers in Immunology, 2024)
Similar to other RNA viruses, grass carp reovirus, the causative agent of the hemorrhagic disease, replicates in cytoplasmic viral inclusion bodies (VIBs), orchestrated by host proteins and lipids. The host pathways that facilitate the formation and function of GCRV VIBs are poorly understood. This work demonstrates that GCRV manipulates grass carp oxysterol binding protein 1 (named as gcOSBP1) and vesicle-associated membrane protein-associated protein A/B (named as gcVAP-A/B), 3 components of cholesterol transport pathway, to generate VIBs. By siRNA-mediated knockdown, we demonstrate that gcOSBP1 is an essential host factor for GCRV replication. We reveal that the nonstructural proteins NS80 and NS38 of GCRV interact with gcOSBP1, and that the gcOSBP1 is recruited by NS38 and NS80 for promoting the generation of VIBs. gcOSBP1 increases the expression of gcVAP-A/B and promotes the accumulation of intracellular cholesterol. gcOSBP1 also interacts with gcVAP-A/B for forming gcOSBP1-gcVAP-A/B complexes, which contribute to enhance the accumulation of intracellular cholesterol and gcOSBP1mediated generation of VIBs. Inhibiting cholesterol accumulation by lovastatin can completely abolish the effects of gcOSBP1 and/or gcVAP-A/B in promoting GCRV infection, suggesting that cholesterol accumulation is vital for gcOSBP1-and/or gcVAP-A/B-mediated GCRV replication. Thus, our results, which highlight that gcOSBP1 functions in the replication of GCRV via its interaction with essential viral proteins for forming VIBs and with host gcVAP-A/B, provide key molecular targets for obtaining anti-hemorrhagic disease grass carp via gene editing technology.